2011
DOI: 10.1038/emboj.2011.168
|View full text |Cite
|
Sign up to set email alerts
|

A hypomorphic IgH-chain allele affects development of B-cell subsets and favours receptor editing

Abstract: The quality and quantity of BCR signals impact on cell fate decisions of B lymphocytes. Here, we describe novel gene-targeted mice, which in the context of normal VDJ recombination show hypomorphic expression of immunoglobulin μ heavy chain (μHC) mRNA levels and hence lower pre-BCR and BCR levels. Hypomorphic expression of μHC leads to augmented selection processes at all stages of B-cell development, noticeably at the expansion of pre-B cells, the positive selection of immature B lymphocytes in the bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…Taken as a whole, our data support a model, first suggested by Nemazee (11) and later on confirmed by studies from other investigators (10,56,57), in which a threshold of tonic BCR signaling is required to prevent receptor editing and lead to positive selection of immature B cells. Behrens and coworkers extended this model, suggesting that autoreactive immature B cells undergo editing because they lack tonic BCR signaling and not because they experience antigen-induced BCR signaling (28).…”
Section: Discussionsupporting
confidence: 76%
“…Taken as a whole, our data support a model, first suggested by Nemazee (11) and later on confirmed by studies from other investigators (10,56,57), in which a threshold of tonic BCR signaling is required to prevent receptor editing and lead to positive selection of immature B cells. Behrens and coworkers extended this model, suggesting that autoreactive immature B cells undergo editing because they lack tonic BCR signaling and not because they experience antigen-induced BCR signaling (28).…”
Section: Discussionsupporting
confidence: 76%
“…Besides a minor decrease in mature splenic B cells, we detected a strong reduction in peritoneal B1 cells in Akt1 Tg mice, which seems to reflect the enhanced sensitivity of B1 cells against altered BCR signals [34,35]. Interestingly, the decline of peritoneal B1 cells in younger Akt1 Tg mice was mainly due to a loss of B1b cells.…”
Section: Discussionmentioning
confidence: 67%
“…Since PI3K signaling has been proposed to regulate class switching [15,33], it is feasible that Akt1-mediated alterations in the expression levels of NF-κB, NFAT, and STAT5 influence the activity of activation-induced cytidine deaminase and other enzymes or of transcription factors involved in class switching. Further studies will also be needed to clarify whether besides altered BCR signaling, an altered in vivo migratory response or a survival advantage of Akt1 Tg B cells might contribute to the enhanced Ig production of Akt1 Tg B cells.Besides a minor decrease in mature splenic B cells, we detected a strong reduction in peritoneal B1 cells in Akt1 Tg mice, which seems to reflect the enhanced sensitivity of B1 cells against altered BCR signals [34,35]. Interestingly, the decline of peritoneal B1 cells in younger Akt1 Tg mice was mainly due to a loss of B1b cells.…”
mentioning
confidence: 67%
“…Weak BCR signaling leads to MZ B cell development, whereas strong signaling is required for FO B cells. Although previous reports clearly showed that the intracellular and surface Igm H chain expression affects B cell subset differentiation (24,36), Akirin2 was dispensable for the direct control of Igm H chain expression. Given that Akirin2 is required for upregulation of a set of NF-kB-dependent genes, it is theoretically possible that Akirin2-dependent genes are critical for the cell fate decision of FO and MZ B cells.…”
Section: Discussionmentioning
confidence: 78%